Coal and fuel burning effects on the atmosphere as mediated by the atmospheric electric field and galactic cosmic rays flux - Reis, A. Heitor (2012)
Abstract: Emissions into the atmosphere of Greenhouse Gases (GHGs) and particulate matter resulting from fossil fuel burning are considered to be the main anthropogenic forcing on the global climate. We show here that the external cyclic influences of cosmic origin that modulate the earth’s climate may either reinforce or mitigate the ‘local’ terrestrial forcings. Among the external influences is cosmic radiation, whose intensity shows a cyclic variation of 11 years, accompanying the 11-year cycle of solar activity. We put forward a mechanism to explain how the emission of particulate matter into the atmosphere might influence global lightning activity. With respect to global lightning activity, we show why, during the 11-year cycle, the influence of an increase in particulate matter concentration in the atmosphere may be negligible in some years, while it will be reinforced in other years, depending on the place of the years in the cycle. We also remark that the effect on global warming of fossil fuel burning is also modulated by the cosmic ray flux, whose influence is mediated by the variation that it promotes on the cloud cover.